Persistent anxiety and in-hospital complications after acute coronary syndrome - AbuRuz, Mohannad Eid (International Journal of Health Sciences, 2018)
Objectives: To investigate the effects of pre-event persistent anxiety on in-hospital complications and length of stay in patients who experienced acute coronary syndrome. Methods: This was a prospective study with patients seeking treatment for acute coronary syndrome events. Anxiety was measured two times before the event in 600 patients with pre-existing coronary heart disease. Patients were followed for two years or until they developed an acute coronary syndrome event. One hundred and twenty patients developed acute coronary syndrome events (rate 20%). Complications and length of stay were abstracted from medical records. Results: Persistently non-anxious patients have lower anxiety scores at three months follow up than baseline (mean [SD], 6.1 [0.24] vs 3.9[0.95], P< .01). Patients with persistent anxiety had significantly higher complication rates than non-anxious patients (mean [SD], 0.71 [0.12] vs 0.15[0.11], P < .05). In a multiple logistic regression, persistent anxiety was an independent predictor of complications. Patients who were persistently anxious were at five times higher risk for developing complications (OR=5.0, 95 % CI: 1.27-38.8, P< .05) Conclusion: Anxiety measured up to two years prior to an acute coronary syndrome event was predictive of in-hospital complications. Clinicians caring for patients with coronary heart disease need to be as equally aware of the importance of assessing and treating persistent anxiety as clinicians caring for patients hospitalized for an acute coronary syndrome.